Enhanced interfacial water dissociation on a hydrated iron porphyrin single-atom catalyst in graphene - Scalfi, Laura; Becker, Maximilian R.; Netz, Roland R.; Bocquet, Marie-Laure (Communications chemistry, 2023)
Single Atom Catalysis (SAC) is an expanding field of heterogeneous catalysis in which single metallic atoms embedded in different materials catalyze a chemical reaction, but these new catalytic materials still lack fundamental understanding when used in electrochemical environments. Recent characterizations of non-noble metals like Fe deposited on N-doped graphitic materials have evidenced two types of Fe-N 4 fourfold coordination, either of pyridine type or of porphyrin type. Here, we study these defects embedded in a graphene sheet and immersed in an explicit aqueous medium at the quantum level. While the Fe-pyridine SAC model is clear cut and widely studied, it is not the case for the Fe-porphyrin SAC that remains ill-defined, because of the necessary embedding of odd-membered rings in graphene. We first propose an atomistic model for the Fe-porphyrin SAC. Using spin-polarized ab initio molecular dynamics, we show that both Fe SACs spontaneously adsorb two interfacial water molecules from the solvent on opposite sides. Interestingly, we unveil a different catalytic reactivity of the two hydrated SAC motives: while the Fe-porphyrin defect eventually dissociates an adsorbed water molecule under a moderate external electric field, the Fe-pyridine defect does not convey water dissociation. Single-atom catalysts (SACs) are highly promising materials for applications such as electrocatalytic water splitting, but coordination geometries around catalyst centers remain the subject of debate. Here, the authors use spin-polarized ab initio molecular dynamics simulations to compare the aqueous reactivities of iron porphyrin and iron pyridine SACs embedded in graphene, and predict the interfacial water dissociative adsorption mechanism under a moderate electric field for an iron porphyrin SAC.